Implementing access to medication assisted treatment in a drug treatment court: Correlates, consequences, and obstacles. Issue 3 (3rd April 2019) - Fendrich, Michael; LeBel, Thomas P.
Abstract: We sought to understand the implementation of medication-assisted treatment (MAT) access for opioid-involved participants in an urban Midwestern drug treatment court (DTC) over a time period beginning in October 2012 and ending in June 2016. Among those whose primary substance problem on the Addiction Severity Index (ASI) was identified as heroin or other opioids, less than half accessed MAT while they participated in the DTC. Those who accessed MAT were more likely to be White, non-Hispanic, more highly educated, with more in-program violations, and less likely to have a history of inpatient psychiatric treatment. Of the three types of medication (buprenorphine, naltrexone, and methadone) accessed, extended release, injectable naltrexone was the most common treatment. There was no association between accessing MAT and program completion. Nevertheless, there was a trend suggesting that those accessing specifically methadone in Opioid Treatment Programs (OPTs) had more success in completing DTC. Our analyses, which are informed by qualitative observations of staff from meetings and interviews and from focus groups with participants, suggest the importance of strategies for enhancing DTC court staff training on opioid disorders and related treatments.